Effect of Assertiveness Training on Adaptive and Aggressive Assertiveness in Nurses - Gila Shaikhpoor; Mohamad Hossein Mafi; Maryam Mafi; Ali Amiri; Seyedeh Zahra Hosseinigolafshani (The Journal of Qazvin University of Medical Sciences, 2020)
Background: Assertiveness is one of the most important skills needed by nurses to reduce interpersonal conflict and build an effective teamwork in complex hospital environments. Objective: The aim of this study was to determine the effect of an assertiveness training program on nurses’ aggressive and adaptive assertiveness. Methods: In this interventional study, participants were 64 nurses working in hospitals of Abhar city in Iran, randomly divided into two groups of intervention (n=32) and control (n=32). Assertive training program was presented as a two-day training workshop (10 hours) to the intervention group, while the control group received no training. Thompson and Burnham’s Adaptive and Aggressive Assertiveness Scale were completed by the participants in both groups at baseline, immediately, one and three months after the intervention. After collecting the data, Friedman, Mann–Whitney, Chi-squared, and Fisher tests were used for their analysis. Findings: The mean of adaptive assertiveness score was significantly different between the the two groups immediately (P=0.002) and 1 month after the intervention (P=0.025). The aggressive assertiveness scores were not significantly different immediately, 1 and 3 months after the intervention (P>0.05), but the results of Friedman test showed a statistically significant decrease in the aggressive assertiveness scores compared to its baseline score (P=0.002). Conclusion: The assertiveness training program increased adaptive assertiveness and decreased aggressive assertiveness in nurses. Relevant authorities can design continuous and useful assertiveness training programs to promot this valuable skill in nurses.